2017
DOI: 10.1007/s40473-017-0113-x
|View full text |Cite
|
Sign up to set email alerts
|

Prosocial Behavior and Depression: a Case for Developmental Gender Differences

Abstract: Purpose of Review Prosocial behavior and depression are related constructs that both increase during adolescence and display gender-specific effects. The current review surveys literature examining the association between depressive symptoms and prosociality, measured with behavioral economic paradigms, across development and proposes a theoretical model explaining a mechanism through which adolescent girls have higher risk for depression than boys. Recent Findings Relative to healthy controls, prosocial beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 98 publications
1
28
1
Order By: Relevance
“…In the trust game, a trustor can allocate resources to a trustee. Subsequently, these resources are augmented by a given factor and finally the trustee must decide how many resources to return to the trustor (Alarcón & Forbes, ) . Most importantly for the present purposes, a recent study using multiple trials of a single‐shot trust game found that postinstitutionalized, adopted youth displayed lower rates and maintained less sharing behavior after they interacted with nonreciprocating peers, compared to never‐institutionalized, nonadopted controls (Pitula, Wenner, Gunnar, & Thomas, ).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the trust game, a trustor can allocate resources to a trustee. Subsequently, these resources are augmented by a given factor and finally the trustee must decide how many resources to return to the trustor (Alarcón & Forbes, ) . Most importantly for the present purposes, a recent study using multiple trials of a single‐shot trust game found that postinstitutionalized, adopted youth displayed lower rates and maintained less sharing behavior after they interacted with nonreciprocating peers, compared to never‐institutionalized, nonadopted controls (Pitula, Wenner, Gunnar, & Thomas, ).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, institutionalization and/ or adoption may engender a distinct pattern of social behavior (e.g., involving limited social reciprocity) that is not typically linked with maltreatment without placement in foster care or adoption (see Zeanah & Gleason, ). Furthermore, while a single‐shot trust game accurately estimates a disposition to trust in a dyadic context (Alarcón & Forbes, ), it cannot account for key aspects of more advanced group‐level cooperation over multiple trials (e.g., higher motivation to cooperate; Axelrod, ; Blake, Rand, Tingley, & Warneken, ). In the present research, we therefore implemented an iterative group‐level PGG to capture effects of maltreatment on cooperative behavior across multiple interactions with the same coplayers.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Increases in prosocial behaviors over time may underlie the observed improvement in global functioning within the RES group, and points to the potentially critical role of prosocial behaviors during this critical stage of emotional development. Previous studies have pointed to the protective factors of prosocial behaviors against the development of psychopathology (Alarcón & Forbes, 2017;Dang, 2014;Silk et al, 2007).…”
Section: Coherence Between Strengths and Difficulties And Global Funcmentioning
confidence: 99%